Developmental Dyslexia vs. Japanese Writing Systems’ Neuronal Processing - Dyszy-Chudzińska, Patrycja (Investigationes Linguisticae, 2009)
This paper is an attempt to explain the neuronal processes engaged in Japanese writing systems processing and its role in developmental dyslexia in the Japanese language. It deals with the question of the hemispheric processing in the Japanese language and explains the mechanisms of developmental dyslexia in the language under discussion. The processes of reading and writing in Japanese will also be presented as they are crucial to a more in-depth understanding of the condition of developmental dyslexia in the Japanese language.